Blue LED Irradiation of Iodonium Ylides Gives Diradical Intermediates for Efficient Metal‐free Cyclopropanation with Alkenes. (26th September 2019) - Chidley, Tristan; Jameel, Islam; Rizwan, Shafa; Peixoto, Philippe A.; Pouységu, Laurent; Quideau, Stéphane; Hopkins, W. Scott; Murphy, Graham K.
Abstract: A facile and highly chemoselective synthesis of doubly activated cyclopropanes is reported where mixtures of alkenes and β‐dicarbonyl‐derived iodonium ylides are irradiated with light from blue LEDs. This metal‐free synthesis gives cyclopropanes in yields up to 96 %, is operative with cyclic and acyclic ylides, and proceeds with a variety of electronically‐diverse alkenes. Computational analysis explains the high selectivity observed, which derives from exclusive HOMO to LUMO excitation, instead of free carbene generation. The procedure is operationally simple, uses no photocatalyst, and provides access in one step to important building blocks for complex molecule synthesis. Abstract : Doppelt aktivierte Cyclopropane entstehen durch Bestrahlung von Alkenen und von β‐Dicarbonyl abgeleiteten Iodonium‐Yliden mit sichtbarem Licht blauer LEDs. Diese metallfreie Cyclopropansynthese funktioniert mit cyclischen und acyclischen Yliden und elektronisch diversen Alkenen in Ausbeuten bis 96 %. Eine Computeranalyse stützt einen Mechanismus basierend auf ausschließlicher HOMO‐zu‐LUMO‐Anregung anstelle der Erzeugung freier Carbene.